2011
DOI: 10.5415/apallergy.2011.1.2.64
|View full text |Cite
|
Sign up to set email alerts
|

Current status of atopic dermatitis in Japan

Abstract: Atopic dermatitis (AD) is a common, chronic or chronically relapsing, severely pruritic, eczematous skin disease. AD is the second most frequently observed skin disease in dermatology clinics in Japan. Prevalence of childhood AD is 12-13% in mainland Japan; however, it is only half that (about 6%) in children from Ishigaki Island, Okinawa. Topical steroids and tacrolimus are the mainstay of treatment. However, the adverse effects and emotional fear of long-term use of topical steroids have induced a "topical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 33 publications
(45 reference statements)
2
38
0
Order By: Relevance
“…7 This can be compared to a 12%-13% prevalence of childhood AD (6-13 years of age) in the Japan mainland. 15 Likewise, the prevalence of eczema in US children at 0 to 17 years of age is 10.7%, 13 while the point prevalence of flexural eczema is 14.2% in 8-to 12-year-old schoolchildren in Sweden. 16 AD was found to be associated with income level, age, and place of residence.…”
Section: Discussionmentioning
confidence: 99%
“…7 This can be compared to a 12%-13% prevalence of childhood AD (6-13 years of age) in the Japan mainland. 15 Likewise, the prevalence of eczema in US children at 0 to 17 years of age is 10.7%, 13 while the point prevalence of flexural eczema is 14.2% in 8-to 12-year-old schoolchildren in Sweden. 16 AD was found to be associated with income level, age, and place of residence.…”
Section: Discussionmentioning
confidence: 99%
“…When broken down by country, higher prevalence (>10%) was seen in children between 6 and 7 years of age in Thailand, Malaysia and South Korea, whereas lower prevalence (<5%) was seen in Hong Kong, Pakistan, Indonesia, India, Syria, Iran, Oman and Vietnam . While Japan was not included in ISAAC, a study conducted in Japanese patients by the Japanese Ministry of Health, Labor and Welfare during a similar timeframe (2000–2002) found that prevalence of AD in children aged 6–7 years was 11.8% . In ISAAC, for children between 13 and 14 years of age, higher prevalence (>10%) was seen in Pakistan whereas lower prevalence (<5%) was seen in Taiwan, India, Hong Kong, Vietnam, Indonesia, Syria, Iran and China (Fig.…”
Section: Ad Epidemiology In Asiamentioning
confidence: 99%
“…13 The number of patients with adult AD (over 40 years of age) has decreased rapidly, 14,16 but the occurrence of AD in senile or elderly patients is also currently an important issue.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The prevalence or incidence of AD in the first five years of childhood is 10%-16.5% and is generally considered to be increasing worldwide, at least from the 1980s to early 2000s. [13][14][15] Most pediatric AD cases are mild-to-moderate in severity, with 84% of cases considered mild, 14% moderate, and only 2%…”
Section: Introductionmentioning
confidence: 99%